Rhenium(i) complexation–dissociation strategy for synthesising fluorine-18 labelled pyridine bidentate radiotracers. Issue 15 (28th February 2020) - Klenner, Mitchell A.; Zhang, Bo; Ciancaleoni, Gianluca; Howard, James K.; Maynard-Casely, Helen E.; Clegg, Jack K.; Massi, Massimiliano; Fraser, Benjamin H.; Pascali, Giancarlo
Abstract : A novel fluorine-18 radiolabelling method employing rhenium(i ) mediation is described herein. In less than 1 minute, fluorine-18 labelled complexes and ligands were synthesised in greater than 80% and 60% radiochemical yields (RCY), respectively. Abstract : A novel fluorine-18 method employing rhenium(i ) mediation is described herein. The method was found to afford moderate to high radiochemical yields of labelled rhenium(i ) complexes. Subsequent thermal dissociation of the complexes enabled the radiosynthesis of fluorine-18 labelled pyridine bidentate structures which could not be radiofluorinated hitherto. This rhenium(i ) complexation–dissociation strategy was further applied to the radiosynthesis of [ 18 F]CABS13, an Alzheimer's disease imaging agent, alongside other 2, 2′-bipyridine, 1, 10-phenanthroline and 8-hydroxyquinoline labelled radiotracers. Computational modelling of the reaction mechanism suggests that the efficiency of rhenium(i ) activation may be attributed to both an electron withdrawal effect by the metal center and the formation of an acyl fluoride intermediate which anchors the fluoride subsequent to nucleophilic addition.